Microbial safety and quality evaluation of UV-Treated, cold-pressed colored and turbid juices and beverages - Usaga Barrientos, Jessie (2018)
The growing demand for fruit and vegetable juice blends, with improved nutritional and sensory attributes, has prompted the industrial adoption of nonthermal processing technologies, including UV light. Limited studies have explored conditions to overcome the well-known limitations of UV when treating liquid foods with a high content of particles that absorb or scatter UV light. This study addressed the effectiveness of the application of UV light, using a commercial processing unit, to inactivate pathogenic Escherichia coli O157:H7, Salmonella enterica (hereafter Salmonella), and Listeria monocytogenes, as well as spoilage microorganisms, in colored and turbid juices and beverages. The inactivation of cocktails of five strains (or serotypes) of E. coli O157:H7, Salmonella, and L. monocytogenes isolated from fruit- and vegetable-derived products linked to outbreaks was determined in seven colored and turbid cold-pressed juices and beverages. Juices and beverages were UV treated at a constant flow rate of 150 L/h through multiple consecutive passes. The inactivation of aerobic mesophilic bacteria, molds and yeasts, and lactic acid bacteria was also assessed at the cumulative dose that guaranteed a 5-log reduction of the most UV-tolerant pathogen for each product. A 5-log reduction of the three pathogens was achieved in all juices and beverages at a maximum cumulative UV dose of 12.0 ± 0.6 mJ/cm2. The dose required to ensure the targeted reduction varied depending on the tested product and the inoculated pathogen. The reduction of aerobic mesophiles, molds and yeasts, and lactic acid bacteria varied from 0.5 to 3.6, from 0.2 to 2.0, and from 0.5 to 3.6 log CFU/mL, respectively. Thus, the proposed treatment represents a suitable processing alternative to ensure the safety and extend the shelf life of colored and turbid cold-pressed juices and beverages.